Investigasi Perilaku Compulsive Buying Berdasarkan Pembayaran Non-Tunai, Lingkungan Sosial, dan Kondisi Keuangan - Berto Mulia Wibawa; Malvin Piero; Ribka Anintha Miyagi (JURNAL SOSIAL HUMANIORA (JSH), 2020)
The behavior of people living in Surabaya is different from people from other cities, including the shopping behavior of the students in Surabaya. Students in Surabaya have more temptation to behave negatively in shopping. It encourages the occurrence of irregularities in shopping. Such action is classified as compulsive buying. Compulsive buying is a spending behavior based on a strong desire that makes people lose consciousness and can not control themself. This study aims to analyze the effect of sales promotion, cashless payment, social environment, and financial condition on compulsive buying on university students in Surabaya. The method used is descriptive analysis with multiple cross-sectional designs. Data were analyzed with Structural Equation Modeling. The result of this research showed that sales promotion, cashless payment, and financial condition variables have a positive effect on compulsive behavior on university students in Surabaya